Development of Thin Electroless Copper Plating Solution Using Glyoxylic Acid as Reducing Agent and its Practical Use - MABUCHI, Katsumi; AKAHOSHI, Haruo (Hyōmen gijutsu, 2020)
As a formaldehyde-free electroless copper plating bath for thin conductive covering inside through-holes of printed circuit boards, this study evaluated a room-temperature glyoxylic acid and Cu-ethylenediaminetetraacetic acid（EDTA）system. Electrochemical behavior was analyzed through polarization curves obtained on Cu plate with three baths:（a）a Cu-ion bath without glyoxylic acid,（b）a glyoxylic acid only bath without Cu-ion, and（c）a completely electroless bath containing all components. They showed similar behavior to that of the Cu-EDTA system using formaldehyde as a reducing agent. The Cu-ion concentration was the most effective at improving the plating rate. Three additives were used to improve the bath stability: K2S, 2-2‘-bipyridyl, and polyethylene glycol. The following items were found to be important to achieve a sufficient level of through-hole coverage: i）maintaining the copper concentration inside the through-hole above a sufficient level, and increasing the bulk Cu-ion concentration and proper agitation; ii）controlling the plating rate using additives of 0.8-2.0 μm / h, even in the high Cu-ion concentration condition. Results demonstrated that glyoxylic acid can replace formaldehyde even in the field of low-temperature thin covering application as the pretreatment of electrolytic through plating. It helps eliminate health and the environmental issues resulting from the widespread use of formaldehyde in the printed circuit board manufacture industry.